The use of convex probe endobronchial ultrasound‐guided transbronchial needle aspiration in a pediatric population: A multicenter study. Issue 8 (13th September 2013) - Gilbert, Christopher R.; Chen, Alexander; Akulian, Jason A.; Lee, Hans J.; Wahidi, Momen; Argento, A. Christine; Tanner, Nichole T.; Pastis, Nicholas J.; Harris, Kassem; Sterman, Daniel; Toth, Jennifer W.; Chenna, Praveen R.; et al.
Summary Introduction The presence of intrathoracic lymphadenopathy and mediastinal masses in the pediatric population often presents a diagnostic challenge. With limited minimally invasive methodologies to obtain a diagnosis, invasive sampling via mediastinoscopy or thoracotomy is often pursued. Endobronchial ultrasound transbronchial needle aspiration (EBUS‐TBNA) is a minimally invasive, outpatient procedure that has demonstrated significant success in the adult population in the evaluation of such abnormalities. Within the pediatric literature there is limited data regarding the use of EBUS‐TBNA. We report the first multicenter review of a pediatric population undergoing EBUS‐TBNA procedures identifying the feasibility, safety, utility, and outcomes of this procedure. Methods All patients of 18 years of age or younger undergoing EBUS‐TBNA at six major academic medical centers from the years 2007 through 2013 were reviewed. Data regarding procedural performance, outcomes, and complications were recorded. Results A total of 21 patients meeting the inclusion criteria were identified in six centers. The mean age of the cohort was 13.7 (±4.1) years. EBUS‐TBNA provided adequate sampling in 20/21 (95%) of the cases with diagnostic material obtained in 10 (48%) cases. Eight patients (38%) underwent additional surgical procedures to confirm or obtain diagnostic tissue. Within our cohort, 13 patients (62%) were able to avoid invasive surgical biopsy procedures. No procedural or anesthesia related complications were identified. Conclusion We report the first multicenter study to date confirming the feasibility and utility of EBUS‐TBNA in the pediatric population. Due to the low overall procedural risk of EBUS‐TBNA, it should be considered as a potential first line diagnostic option for children presenting with mediastinal or hilar abnormalities but further prospective studies are needed. Pediatr Pulmonol. 2014; 49:807–815. © 2014 Wiley Periodicals, Inc.